2020
DOI: 10.1080/09540105.2020.1786672
|View full text |Cite
|
Sign up to set email alerts
|

Progress in immunoassays for nitrofurans detection

Abstract: Nitrofurans comprise a class of synthetic broad-spectrum antibacterial agents, which had been used extensively as therapeutic drugs and feed additives in animal husbandry. Because of the potential carcinogenic and mutagenic effects of these drugs and their metabolites, most countries have banned their use in food animals. However, driven by economic interests, the illegal use of nitrofurans poses a significant threat to human health. Therefore, to safeguard health of the consumer, it is of paramount importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Wu et al et al ( Wu et al, 2020 ) gave a detailed introduction to ELISA studies to detect AOZ, SEM, AHD, and AMOZ before 2020. Yan et al ( Yan et al, 2020b ) combined Au NPs into conventional ELISA for sensitive detection of AMOZ, thereby improving detection sensitivity.…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…Wu et al et al ( Wu et al, 2020 ) gave a detailed introduction to ELISA studies to detect AOZ, SEM, AHD, and AMOZ before 2020. Yan et al ( Yan et al, 2020b ) combined Au NPs into conventional ELISA for sensitive detection of AMOZ, thereby improving detection sensitivity.…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…Nitrofurans break down rapidly in the organism, and their metabolites bind to proteins, including those in muscle tissue, and can persist there for several weeks [ 14 , 15 ]. Nitrofurans have four persistent metabolites (NM): 3-amino-2-oxazolidinone (AOZ), 3-amino-5-methylmorpholino-2-oxazolidinone (AMOZ), 1-aminohydantoin (AHD), and semicarbazide (SEM) [ 16 ]. AOZ is a marker metabolite for furazolidone, AMOZ—for furaltadone, AHD—for nitrofurantoin, and SEM—for nitrofurazone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicology research indicated that NFs and their metabolites are potentially hazardous substances, with possible carcinogenic, teratogenic, and mutagenic properties [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%